Consumers' preference towards food truck business: a case study in Penang / Suria Sulaiman ... [et al.] - Nik Mohd Nor, Nik Mohd Shahril; Ab Rashid, Putri Dahlia; Azren, Muhamad Hafiz (2021)
The food truck business in the food and beverage industry is notably a highly competitive field. It is the most convenient food service and offers a variety of common local food. However, being able to fulfill customer expectations and demands becomes the most essential element to sustain growth and increase profit margin in this business. Thus, this research's objective is to investigate the consumers' preference towards the food truck business by focusing on three factors: variation of food, price, and the trends of the food truck business. This study is significant in supporting food truck activities and helping both vendors and customers to understand more on the variables that attracted them to the food truck market. A cross-sectional survey was carried out at higher educational institutions in Penang. The questionnaires were distributed to students who have experience buying a product from food truck. A total of 400 questionnaires were distributed during the data collection procedure and out of these 300 questionnaires were completed and returned. The research found that there is a significant relationship between all factors toward consumers' preference for food truck business. Therefore, it can be concluded that students have positive views towards food trucks and will continuously support the business as long as their preferences and demands can be fulfilled by the vendors. This study can be used as a reference for the food truck vendors in addressing the weaknesses and fulfilling the demand to remain competitive in the industry.